Bridging the Chinese Language Curriculum in Thailand: Alignment and Development Strategies for Transitioning from Secondary to the Expectations of Higher Education - Pornrattananukul, Apisara (Journal of Education Studies, Chulalongkorn University, 2025)
This study aimed to 1) analyze and compare the alignment of content standards, competency standards, and language proficiency levels between the Chinese language learning standards in Thailand’s Basic Education Core Curriculum (2008) at the upper secondary level and the Chinese Proficiency Grading Standards for International Chinese Language Education at the elementary level (implemented on July 1, 2021); 2) propose a set of guidelines for developing secondary-school Chinese language curricula that articulate with the Chinese Proficiency Standards for International Chinese Language Education at Level 3 (issued in 2021). The research utilized a custom-designed content analysis form. The analysis focused on three dimensions: presence of content, characteristics of content, and level of coverage. The data were analysed using qualitative coding, and the validity of the tool was verified through inter-rater reliability by comparing results between the researcher and a rater. The findings revealed a clear overlap in the structural components of language skills—listening, speaking, reading, and writing—and a shared tendency toward sequential skill development. However, differences were observed in the depth of content, the way learning outcomes were described, and the use of quantitative performance indicators. The results support the use of HSK as a reference framework for curriculum structuring to link language learning across educational levels. The study also proposes a direction for developing the secondary-level Chinese language curriculum that effectively transitions into higher education by integrating the strengths of both the national standard-based education system and international language proficiency benchmarks.